Предмет: Математика,
автор: thediaна
Розкладіть на множники :
-x^2-x+6
Ответы
Автор ответа:
2
-x^2-x+6=-(х-х1)*(х-х2)=-(х-(-3))*(х-2)=-(х+3)*(х-2)=(х+3)*(-х-(-2))=(х+3)*(2-х)
-x^2-x+6=0|*(-1)
x^2+x-6=0
По теореме Виета:
х1+х2=-1
х1*х2=-6
х1=-3
х2=2
-x^2-x+6=0|*(-1)
x^2+x-6=0
По теореме Виета:
х1+х2=-1
х1*х2=-6
х1=-3
х2=2
2407Alexa:
Не за что!
Похожие вопросы
Предмет: Кыргыз тили,
автор: askhatkorlanov25
Предмет: Математика,
автор: viktoriia201053
Предмет: Русский язык,
автор: Аноним
Предмет: Математика,
автор: sve8166866
Предмет: Математика,
автор: Катя100605